Crystallization of GeSn thin films deposited on Ge(100) substrate by magnetron sputtering. (December 2018) - Wang, Yisen; Zhang, Lu; Huang, Zhiwei; Li, Cheng; Chen, Songyan; Huang, Wei; Xu, Jianfang; Wang, Jianyuan
Abstract: The influence of growth temperature and Sn content on crystallization of GeSn on Ge substrate prepared by magnetron sputtering was investigated. Single crystal GeSn thin films with Sn content of 1–3.4% were achieved with rapid thermal annealing at 600 °C for the initial sputtered amorphous GeSn at relatively lower deposition temperature(180–350 °C), while polycrystalline GeSn thin films were formed for the GeSn having been crystallized during deposition process at higher deposition temperature(≧450 °C). It was demonstrated that the sputtered amorphous GeSn could be solid phase crystallized on Ge substrate at high annealing temperature. In contrast, insufficient atom migration at low annealing temperature or multi-nucleation during sputtering process at higher growth temperature rendered the polycrystalline GeSn films. The crystallization temperature of GeSn thin film decreases with increase of Sn/Ge ratio in the sputtered GeSn films, while the Sn composition in the crystallized GeSn alloys is dominated by annealing temperature due to severe tin segregation.